Leadership in Islamic Schools in Scientific Literature: A Bibliometric Analysis - Hilmiatussadiah, Kinanti Geminastiti; Disman, Disman; Ahman, Eeng; Mulyani, Heni (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
This study aims to map and conceptualise the development of research on school leadership in Islamic schools through a bibliometric approach. This study analyses 150 internationally indexed scientific articles using citation analysis, keyword co-occurrence, and thematic mapping to identify publication trends, research focus, scientific structure, and dominant geographical context in Islamic school leadership research. The analysis shows that studies on Islamic school leadership have increased significantly over the last two decades, with a strong emphasis on spiritual leadership, religious values, moral legitimacy, and character development. These findings indicate that Western educational leadership theories, such as instructional, transformational, and distributed leadership, have limitations in explaining Islamic school leadership practices rooted in belief systems and spiritual values. The theoretical contribution of this study lies in affirming Islamic school leadership as an integrative, contextual model that combines managerial, pedagogical, and spiritual dimensions. Conceptually, this study expands the discourse on educational leadership by presenting a non-Western perspective grounded in values and beliefs (faith-based leadership), while also closing a research gap by providing a comprehensive mapping of the scientific landscape of Islamic school leadership as a basis for further in-depth, contextual research. The conclusion of this study affirms that Islamic school leadership is an integrative model grounded in religious and spiritual values, distinct from the Western leadership paradigm. This leadership is not only oriented toward school effectiveness but also toward safeguarding the ethical and transcendent mission of Islamic education.